The equation of a circle with the center at (h, k) and radius r given by the general formula:

(x – h)^2 + (y – k)^2 = r2

k= 4

r = 7

So the equation will be (x - 8)^{2} + (y -4)^{2} = 49

I am expanding.....I will submit within 3 mins

(x - 8)2 + (y -4)2 = 49

(x - 8)2 = x2 -16x + 64

(y -4)2 = y2 - 8y + 16

x2 + y2 -16x -8y + 64 +16 = 49

x2+y2-16x -8y+ 80-49=0

x2 + y2 -16x -8y +31 = 0.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up